Solitary coronary artery: An unusual cause of atypical chest pain - Dubey, Laxman; Adhikari, Ridhi; Deep, Suresh (Nepalese Heart Journal, 2019)
Coronary arteries arising from single coronary sinus is a rare congenital anomaly. We report a 30-year-old male who presented with atypical chest pain and computed tomography coronary angiography revealed a solitary coronary artery originating from a single ostium in the right sinus of Valsalva.